Pengaruh Budaya Organisasi dan Lingkungan Kerja terhadap Kinerja Karyawan PT Tirta Investama Distribution Center Bandung - Lestari, Delia; I Magi, Bahmid; Mayanti, Yuni (Ma'soem University, 2025)
The background of this study is the issue of organizational culture such as employees who are accustomed to leaving the office prematurely and the work environment such as inadequate storage facilities that cause untidiness in the employee's workspace. This study aims to determine how organizational culture and work environment influence employee performance partially and simultaneously at PT Tirta Investama DC Bandung. The type of research is quantitative with an associative method. The collection technique is through questionnaires, observations and interviews with employees of the company being studied. The population is all production employees at PT Tirta Investama DC Bandung, totaling 114 people with a sample of 54 people. The results of the study at PT Tirta Investama Distribution Center Bandung showed that there was a significant influence of organizational culture on employee performance of 44.4% with the results of t count > t table (6.442 > 1.298) meaning H1 was accepted, there was a significant influence of the work environment on employee performance of 28.1% with the results of t count > t table (4.503> 1.298) meaning H1 was accepted, and simultaneously there was a significant influence between organizational culture and work environment on employee performance of 51% with the results of the F test f count > f table (26.550> 2.19).